PENGARUH METODE BERNYANYI TERHADAP PENGETAHUAN PENDIDIKAN SEKSUAL ANAK USIA 4-5 TAHUN DI TK SHAFA MARWAH - Ramadhani, Daffa; Darmiyanti, Astuti; Riana, Nancy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of sexual education knowledge among children aged 4-5 years at TK Shafa Marwah before and after treatment using the singing method, and to determine the effect of the singing method on the improvement of that knowledge. This study was motivated by the low level of sexual education knowledge among Group A children at TK Shafa Marwah, including the recognition of private body parts, sexual identity, body privacy boundaries, sexual organ health, and self-protection from sexual crimes. This study used a quantitative approach with a Pre-Experimental Design in the form of a One Group Pretest-Posttest Design. The research sample consisted of 30 Group A children selected using the Quota Sampling technique. Data were collected through observation, structured interviews, and documentation using an assessment instrument consisting of 22 statement items. Treatment was given through eight meetings using Islamic-themed educational songs entitled